2016
DOI: 10.4317/medoral.20866
|View full text |Cite
|
Sign up to set email alerts
|

Impact of oral mucosa lesions on the quality of life related to oral health. An etiopathogenic study

Abstract: BackgroundTo assess the impact of oral mucosa lesions on quality of life related to oral health (QLROH) and additionally to establish whether the etiopathogenicy of oral lesion is associated to the degree of QLROH impact.Material and MethodsIn this cross-sectional study performed on a non-probability sample of 247 consecutively patients attending the oral medicine and pathology clinic the Spanish version of Oral Health Impact Profile-49 questionnaire (OHIP-49-mx) was applied. Responses were recorded on Likert-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 20 publications
1
15
2
Order By: Relevance
“…In the present study, the OSMF patients have shown no significant difference of physical health domain of WHO-QOL when compared with the control participants. The results of the present study are contradictory to the results of Villanueva et al [19], Tadakamadla et al [20], where they observed that the quality of the physical factors shows a significant impact on the oral health quality of life. The contradictory results of physical heath domain in the present study to the previous literature might be because of variations in the study samples analyzed, where all the participants of OSMF with no restrictions on clinical severity were included in the present study for evaluation the QOL.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In the present study, the OSMF patients have shown no significant difference of physical health domain of WHO-QOL when compared with the control participants. The results of the present study are contradictory to the results of Villanueva et al [19], Tadakamadla et al [20], where they observed that the quality of the physical factors shows a significant impact on the oral health quality of life. The contradictory results of physical heath domain in the present study to the previous literature might be because of variations in the study samples analyzed, where all the participants of OSMF with no restrictions on clinical severity were included in the present study for evaluation the QOL.…”
Section: Discussioncontrasting
confidence: 99%
“…It infers that QOL was negatively influenced in individuals with OSMF. The present results are in agreement with those obtained in other populations as well [18][19][20]. Further, all the four domains, namely physical, psychological, social and environmental, were further analyzed separately to identify the specific domain in which quality of life of OSMF patients was affected.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…OMLs may include common pathologies and developmental defects such as fibromas, mucoceles, candidiasis, leukoplakia, geographic and fissured tongue, Fordyce granules and in rare cases oral cancers . It is important to emphasize that this large group of alterations may have clinically relevant implications, such as pain, difficulty in eating and speaking, and also aesthetic problems, which may impact an individual's oral health‐related quality of life . The prevalence of OMLs in the general population differs across different regions and countries and ranges from 5% to 65%.…”
Section: Introductionmentioning
confidence: 99%
“…Many oral mucosal conditions significantly influence the patient's quality of life . Timely identification and intervention can therefore reduce morbidity and improve the patient's quality of life.…”
Section: Introductionmentioning
confidence: 99%